Alberti, León, Saslavsky: reinventando “La dama duende” en la Argentina de los exiliados - Pucciarelli, Tiziana (Confluenze. Rivista di Studi Iberoamericani, 2019)
This work focuses on the movie La dama duende made in Argentina in 1945, adapted by María Teresa León and Rafael Alberti and under the direction of Luis Saslavsky. Without moving too far from the original, the film draws from the new setting all its critical potentialities in order to project them on the catastrophe of the Franco dictatorship. In the hands of María Teresa León and Rafael Alberti, the Calderonian comedy is transformed into a great popular spectacle and is a pre-text aimed to engender a political fable where the concept of “las dos Españas” takes shape and movement on the screen.